MRI for Fetal Developmental Brain Abnormalities: Perspectives From the Pregnant Patient. (July 2018) - Lie, Mabel L. S.; Graham, Ruth H.; Robson, Stephen C.; Griffiths, Paul D.
Ultrasound is routinely used as a prenatal screening and diagnostic tool but has limitations. Some anomalies in the developing fetal brain can be difficult to detect, and in utero magnetic resonance imaging (iuMRI) is increasingly used as an adjunct to ultrasound. However, understandings of patient perspectives of iuMRI technology are still developing. Our qualitative study of 41 mothers who experienced iuMRI was embedded in a diagnostic accuracy trial and aimed to inform policy recommendations that might stem from the clinical findings. Our analysis suggests that iuMRI is seen as useful, offering valuable additional information and helping women make decisions about care options at a difficult time. However, patients' experiences demonstrated the uncertainty and anxiety associated with the prenatal diagnosis (PND) process relating to brain anomalies including the challenges of their embodied contributions. Our findings suggest more could be done to reduce the impact on pregnant women during an already difficult, anxious period.